An Argument-Based Validation of an Asynchronous Written Interaction Task - Chen, Ting (Frontiers in Psychology, 2022)
Interactional competence has attracted increasing attention due to its significance for language users. Previous studies concerning interactional competence mainly focus on synchronous interaction tasks, while the utilization of asynchronous interaction tasks is relatively under-explored despite the importance of asynchronous interaction in real life. Taking the “Responding To Forum Posts” (RTFP) task used in the International Undergraduate English Entrance Examination (IUEEE) at Shanghai Jiao Tong University (SJTU) as an example, the study aims to validate the use of asynchronous interaction tasks in the assessment of learner’s interactional competence. 49 students’ performances on the RTFP task were collected through a prototype test of the IUEEE in 2021. The data were analyzed through content analysis, analysis of variance, and ordinal logistic regression. The results showed that the task elicited a wide range of interactional features and test-takers at different proficiency levels differed significantly in the variety of features and the amount of emotion-based interaction. The study also found significant correlations between some of the features and test takers’ overall performance on interactional competence. The study has provided validity evidence for the RTFP task in the assessment of interactional competence and thrown light on the construct of asynchronous written interactional competence.